Commodity Regional Analysis and the Role of Smallholder Arabica Coffee Plantations in the Regional Development of North Sumatra Province - Hendris Syah Putra; Herlyna Novasari Siahaan (Jurnal Ilmiah Membangun Desa dan Pertanian, 2024)
Sustainable development goals now include efforts to achieve economic prosperity for people while complying with international agreements. Evidence has shown that the agricultural sector plays an essential role in driving the Gross Regional Domestic Product (GRDP) of North Sumatra Province in 2022. The plantation crops sub-sector is the most significant contributor to the agricultural business sector. Coffee, an excellent agricultural commodity, is essential in developing neighboring regions. There are many small coffee plantations in North Sumatra, and local communities highly depend on its production. Arabica coffee development should be based on the capacity and prospects of the commodity in the region. The objectives of this study are to (1) describe the main areas where small-scale Arabica coffee producers operate in North Sumatra Province; (2) analyze the distribution patterns of small-scale Arabica coffee producers in North Sumatra Province; and (3) determine the extent to which Arabica coffee producers contribute to regional development. A descriptive-quantitative methodology was used in this study. Information was obtained from secondary data sources for the period 2019-2021. Location quotient (LQ) analysis, specialization, and localization analysis, primary service ratio (BSR), and regional multiplier (RM) analysis were used for data analysis. The analysis results show that Mandailing Natal, South Tapanuli, South Tapanuli, South Tapanuli, and South Tapanuli are the significant regions in the region.